A lower dosage of imatinib is sufficient to maintain undetectable disease in patients with chronic myeloid leukemia with long-term low-grade toxicity of the treatment. Issue 2 (1st February 2016) - Faber, Edgar; Divoká, Martina; Skoumalová, Ivana; Novák, Martin; Marešová, Ivana; Mičová, Kateřina; Friedecký, David; Adam, Tomáš; Jarošová, Marie; Indrák, Karel
Abstract : The information about chronic myeloid leukemia (CML) patients with a deep molecular response of ≥ 4.5 log reduction (MR 4.5 ) in whom the dose of imatinib (IM) had to be reduced to relieve toxicity is insufficient. In 205 CML patients the dose of IM was reduced in 19 (31.2%) out of 61 patients with MR 4.5 . The patients (12 pretreated with interferon-alpha) achieved MR 4.5 after an average of 27.7 months. The duration of MR 4.5 before the reduction of the dose was 16–123 (mean = 56.7) months. After the IM reduction (200 mg daily to 400 mg twice weekly for 15–90 (mean = 48) months) MR 4.5 or major molecular response (MMR) was maintained in 14 (73.7%) and 2 (10.5%) patients, respectively. Three patients who lost MMR (15.8%) after the discontinuation of IM regained MR 4.5 after the reintroduction of a lower dose. A lower dosage of IM should be tested for the management of side effects in patients with MR 4.5 in prospective studies.